Analysis Of Factors Affecting Carbon Emission Disclosure With Good Corporate Governance As A Moderating Variable - Anggun Putri Aprilia; Sri Wahyuni; Hariyanto, Eko; Azizah, Siti Nur (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2026)
This study examines the effects of profitability, company size, and environmental performance on carbon emission disclosure in transportation companies listed on the Indonesia Stock Exchange (IDX) for the period 2020–2024, with GCG as the moderating variable. The study population consisted of 38 companies, and a purposive sample of 27 was selected, yielding 135 data points. This study is based on secondary data from annual and sustainability reports, with analysis using multiple linear regression and Moderated Regression Analysis (MRA) under the classical assumption tests. The results indicate that company size and environmental performance affect carbon emissions disclosure, whereas profitability does not. GCG is proven to strengthen the relationship between profitability and company size, while it does not moderate environmental performance on carbon emissions disclosure. These findings show that GCG plays an essential role in improving the transparency and accountability of carbon emissions reporting.